1974
DOI: 10.1002/dev.420070512
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal adrogen treatment and sexual behavior in males of three inbred strains of mice

Abstract: Male neonates of the A, BABL/c, and C57BL/6 mouse strains were injected with androgen and the effects upon their sex behavior studied. Genotype and treatment combined interactively on a number of variables, particularly in the proportions of animals responding, indicating that the effects of perinatally administered androgen and genotype cannot be considered separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
3
6
0
Order By: Relevance
“…The reduction in testis weights, in the treated animals, is in agreement with the findings of Vale et al (1974) and Bronson and Desjardins (1968). These authors also found decreases in seminal vesicle weights, a result not recorded in this experiment.…”
Section: Discussionsupporting
confidence: 93%
“…The reduction in testis weights, in the treated animals, is in agreement with the findings of Vale et al (1974) and Bronson and Desjardins (1968). These authors also found decreases in seminal vesicle weights, a result not recorded in this experiment.…”
Section: Discussionsupporting
confidence: 93%
“…The finding of intraspecific variation in hormone sensitivity in an outbred, naturally occurring species is similar to findings of strain differences in behavioral sensitivity to exogenously administered androgens (21)(22)(23). Since the animals used in this study were collected from a variety of sites, it remains to be determined whether these results reflect population differences and/or are due to enzyme deficiences in nonresponding individuals (24).…”
Section: Discussionsupporting
confidence: 69%
“…The sex chromosome effect reported here, however, is unlikely to be mediated by group differences in androgen secretion. Had the XY Ϫ genotype caused a greater secretion of testosterone perinatally relative to the XX genotype, the difference in these groups should have been detected in more than one phenotype because most of the phenotypes measured are masculinized by testosterone or its metabolites, probably during different but overlapping critical periods (Vale et al, 1973;Wagner and Clemens, 1989;Wang et al, 1993;Simerly et al, 1997). Thus, each system can be considered a sensitive barometer of levels of gonadal steroids during perinatal development, and the lack of sex chromosome effects in most of the systems is evidence against a sex chromosome effect on the levels of circulating gonadal steroids.…”
Section: Discussionmentioning
confidence: 99%